A study on the presence of harmful bacteria on protective eyewear - Bawagan, Maureen O.
Many routine dental procedures expose both the dentist and patient to serious eye injury. One such procedure is scaling and polishing. In view of this, a study was made on the presence of harmful bacteria on protective eyewear after scaling and polishing. This was done to increase the dentist's awareness of the importance of protective eyewear as a barrier against microorganisms or debris contracted in the dental operatory. Ten Clinicians were asked to perform scaling and polishing and each was provided with a protective eyewear. Swabs were taken from the inner and outer surface of the eyewear before use, after scaling and after washing. The swabs were cultured and various tests were done to identify the bacterial organism present. Results have shown the presence of the following bacteria: Staph, Epidermidis, Bacillus Subtillus, Staph. Aureus, B-hemolytic strep., Psuedomonas, Klebsiella pneumoniae and Serratia Marcesence. Among these organisms, Staph, Aureus and B-hemolytic Strep. were found to be harmful. The other organisms isolated were found to be contaminants coming from the water and inside the dental operatory.